Assessment Of the Carbon Footprint of Household Activities in Kleak, Malalayang District, Manado City - Minanga, Dony T.; Wantasen, Sofia; Lumingkewas, Adeleyda M. W.; Paat, Frangky J.; Rotinsulu, Wiske Ch.; Paulus, Jeanne M.; Pioh, Diane D.; Ogie, Tommy B. (Jurnal Agroekoteknologi Terapan, 2026)
Household energy use and private mobility are important sources of greenhouse-gas emissions in urban residential areas. This study assessed the carbon footprint of household activities in Kelurahan Kleak, Malalayang District, Manado City, Indonesia. The study was conducted from January to March 2026 using a field-based survey approach with purposive sampling. A total of 354 households were selected from six neighbourhood units (lingkungan). Primary data were collected through direct observation and questionnaires covering LPG consumption, electricity use, vehicle ownership, fuel type, and fuel consumption. Carbon emissions were estimated for three major household-related sources, namely LPG use, electricity consumption, and private transportation fuel use, using IPCC-based emission calculation methods. The results showed that the total household carbon footprint of Kelurahan Kleak reached 6,599.65 ton CO₂eq year⁻¹. Transportation fuel was the largest contributor, accounting for 3,609.97 ton CO₂eq year⁻¹, followed by electricity consumption at 2,613.89 ton CO₂eq year⁻¹, while LPG use contributed 375.80 ton CO₂eq year⁻¹. Among the six neighbourhoods, Lingkungan 6 produced the highest total emissions at 2,123.05 ton CO₂eq year⁻¹, equivalent to 32.17% of the total carbon footprint. These findings indicate that household carbon emissions in Kelurahan Kleak were driven primarily by private mobility and electricity use rather than cooking fuel consumption. The study provides baseline evidence for neighbourhood-scale carbon management and highlights the importance of community-based mitigation strategies in urban residential environments. Keywords: carbon footprint; electricity consumption; household activities; LPG use; transportation fuel